The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1159/000118031
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Portacaval Shunt on Reperfusion Injury after 65% Hepatectomy in Pigs

Abstract: Background: Portal flow diversion by portacaval shunts (PCS) has been shown to prevent primary graft nonfunction in liver transplantation using small-for-size grafts. In this study, we examine whether PCS can improve reperfusion injury after major hepatectomy in pigs. Materials and Methods: In 14 pigs, a partial PCS was constructed following 65% hepatectomy and 1 h of inflow ischemia. During 24 h of reperfusion, the shunt was either closed (group A, n = 7) or left open (group B, n = 7). Results: 24 h after rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Hematoxylin-eosin (H & E) staining demonstrated mixed small and large hepatocyte nuclei, and accumulations of fatty globules in hepatocytes following PH; this anisokaryosis and simultaneous fatty degeneration indicates both regenerative and degenerative changes in the hepatocytes 25 , 26 . These effects were detected 10 and 17 days after PH in RS-treated animals, while they were already present after only 3 days in controls (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hematoxylin-eosin (H & E) staining demonstrated mixed small and large hepatocyte nuclei, and accumulations of fatty globules in hepatocytes following PH; this anisokaryosis and simultaneous fatty degeneration indicates both regenerative and degenerative changes in the hepatocytes 25 , 26 . These effects were detected 10 and 17 days after PH in RS-treated animals, while they were already present after only 3 days in controls (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…5c–e ). To gain further insights into the regenerative response in pigs exposed to RS, we next quantified the proliferating cell nuclear antigen (PCNA) and Ki-67 expression 25 , 27 , 28 . The number of PCNA-positive cells was significantly higher in RS-treated animals than controls at PH.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, it has been suggested that after extensive hepatectomies, a small liver remnant is vulnerable to functional impairment, probably induced by the enforced diversion of the entire portal flow through a restricted sinusoidal network and the resulting shear stress and congestion of the sinusoidal endothelial lining cells [12][13][14].…”
Section: Introductionmentioning
confidence: 99%